1982
DOI: 10.1007/bf01541595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone replacement on sexual behavior in hypogonadal men

Abstract: Fifteen patients with hypogonadism due to testicular, pituitary, or hypothalamic failure were studied. After a pretreatment period without substitution, patients received intramuscular injections of testosterone enanthate, equivalent to 25, 50, 100, and 250 mg testosterone, or placebo. Each dose was given for 4 weeks, with injections given every 2 weeks. All patients with plasma testosterone values below 2 ng/ml during the pretreatment period reported impaired sexual function. They responded to testosterone in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
3

Year Published

1987
1987
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(58 citation statements)
references
References 5 publications
3
51
1
3
Order By: Relevance
“…Studies by other groups have demonstrated that in both men (34,35) and women (20) above a certain minimal value of FT, increasing levels do not result in increased sexual drive. Thus the women in this study behaved in the same way as women without epilepsy who have been studied elsewhere.…”
Section: Discussionmentioning
confidence: 95%
“…Studies by other groups have demonstrated that in both men (34,35) and women (20) above a certain minimal value of FT, increasing levels do not result in increased sexual drive. Thus the women in this study behaved in the same way as women without epilepsy who have been studied elsewhere.…”
Section: Discussionmentioning
confidence: 95%
“…Other investigators (e.g., Salmimies, Kockott, Pirke, Vogt, & Schill, 1982) have reported that providing testosterone replacement therapy to hypogonadal men leads to increases in the frequency of spontaneous erections. Subsequent, more fine-grained analysis suggests that testosterone may be more important to fantasy-based arousal and sexual desire than it is to externally stimulated erections (Bancroft & Wu, 1983).…”
Section: Endocrine Deficienciesmentioning
confidence: 99%
“…The lack in association is further supported by the observation that testosterone treatment does not significantly alter sexual dysfunction in normogonadotropic men. Merely in hypogonadal men is the sexual activity clearly improved by testosterone substitution, regardless of the mode of application [1,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%